‘Mas Zakky’: Model Zakat Pemberdayaan dari Baznas Kota Yogyakarta - Jaya, Pajar Hatma Indra (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2018)
The model of zakat management in the modern era is divided into two, namely the charity model (consumptive zakat) and the productive zakat model (zakat empowerment). So far, zakat distribution uses a lot of charity models so that it does not give long-term contribution because it is consumptive. Through this article, I would like to explain the marketing of productive zakat (empowerment model) with the name of the program Mas Zakky and see its impact on society. Distribution Mas Zakky’s model is done in four stages, namely the determination of the right muztahiq (recipient program), debriefing, giving power, and mentoring are tightly controlled. This study found that the keyword for the success of the zakat empowerment program is that it should not stop at giving assistance, but must be assisted within one year so that new habits are formed from the mustahiq. The new habit arises because of awareness, habituation, and strict control through monitoring of good financial management, which mustahiq are required to provide daily business reports, monthly profit reports, savings obligations of at least 2.5 percent of gross sales every month, and learn to invest input “sedino sewu” (one day one thousand rupiah) cans in their place of business. Mas Zakky’s program has an impact on the loss of the mustahiq conditions due to the emergence of new jobs, the growing awareness that trading business is a form of profitable work, the emergence of awareness to save, diligently praying Dhuha, the formation of tissue, and the emergence of habits of infaq (donation).Model pengelolaan zakat di era modern dibagi menjadi dua, yaitu model carity (zakat konsumtif) dan model zakat produktif (zakat pemberdayaan). Selama ini penyaluran zakat banyak menggunakan model carity sehingga kurang memberi kontribusi jangka panjang karena sifatnya konsumtif. Melalui artikel ini penulis hendak menjelaskan pentasarufan zakat produktif (model pemberdayaan) dengan nama program Mas Zakky dan melihat dampaknya bagi masyarakat. Pentasarufan model Mas Zakky dilakukan dengan empat tahap, yaitu penentuan muztahak yang tepat, pembekalan, pemberian daya, dan pendampingan yang terkontrol secara ketat. Penelitian ini menemukan bahwa kata kunci keberhasilan program zakat pemberdayaan adalah tidak boleh berhenti pada pemberian bantuan, namun harus dilakukan pendampingan dalam waktu satu tahun sehingga terbentuk kebiasaan baru dari para mustahik. Kebiasaan baru tersebut muncul karena penyadaran, pembiasaan, serta kontrol ketat lewat pemantauan tentang manajemen keuangan yang baik, yangmana mustahik diwajibkan untuk memberikan laporan usaha harian, laporan keuntungan bulanan, kewajiban menabung minimal 2,5 persen dari penjualan kotor setiap bulan, dan belajar berinfaq dengan menaruh kaleng “sedino sewu” di tempat usaha mereka. Program Mas Zakky berdampak pada mulai hilangnya kondisi fakir para mustahik karena munculnya pekerjaan baru, tumbuhnya kesadaran bahwa usaha dagang merupakan bentuk pekerjaan yang menguntungkan, munculnya kesadaran untuk menabung, rajin sholat dhuha, terbentuknya jaringan, dan munculnya kebiasaan berinfak.